2013
DOI: 10.1002/chem.201300201
|View full text |Cite
|
Sign up to set email alerts
|

Unique Structural Properties of 2,4,6‐Tri‐tert‐butylanilide: Isomerization and Switching between Separable Amide Rotamers through the Reaction of Anilide Enolates

Abstract: Herein, we report a unique structural property of 2,4,6-tri-tert-butylanilide, which can be separated into its amide rotamers at room temperature. Interconversion between the rotamers of anilide enolates occurs readily at room temperature and their reaction with electrophiles gives mixtures of the rotamers in a ratio that depends on the reactivity of the corresponding electrophile. That is, the reaction of the 2,4,6-tri-tert-butylacetanilide enolate with reactive electrophiles, such as allyl bromide or protic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In contrast to 2° amides, for which the trans conformation is nearly universally favored over the cis conformation (as shown in Figures and ), N -alkyl- N -aryl 3° amides demonstrate the opposite conformational preference. Both experimental and computational results from dozens of independent researchers, together studying hundreds examples of N -alkyl- N -aryl 3° amides have clearly identified that the cis conformation is generally favored over the trans conformation by between 0.5 and 5 kcal/mol. Multiple studies have even taken advantage of this conformational preference, using 3° amides as cis backbones for chelating ligands and macromolecular architecture, , for preorganization to facilitate synthesis of lactams, , or for restricting rotation. Okamoto et al synthesized 3° N -pyridyl amides and demonstrated that the conformational preference can switch upon the addition of acid , or in solvents capable of hydrogen bonding …”
Section: Introductionmentioning
confidence: 99%
“…In contrast to 2° amides, for which the trans conformation is nearly universally favored over the cis conformation (as shown in Figures and ), N -alkyl- N -aryl 3° amides demonstrate the opposite conformational preference. Both experimental and computational results from dozens of independent researchers, together studying hundreds examples of N -alkyl- N -aryl 3° amides have clearly identified that the cis conformation is generally favored over the trans conformation by between 0.5 and 5 kcal/mol. Multiple studies have even taken advantage of this conformational preference, using 3° amides as cis backbones for chelating ligands and macromolecular architecture, , for preorganization to facilitate synthesis of lactams, , or for restricting rotation. Okamoto et al synthesized 3° N -pyridyl amides and demonstrated that the conformational preference can switch upon the addition of acid , or in solvents capable of hydrogen bonding …”
Section: Introductionmentioning
confidence: 99%
“…The E / Z -isomerism and atropisomerism of tertiary benzamides, naphthamides and other structural analogues showing restricted rotation about the aryl-carbonyl bond have been studied by Clayden, Walsh, and others and are well-known to play important roles in asymmetric synthesis, medicinal chemistry, and chiral amplification processes . For similar reasons, Curran and others have investigated the relative stability and interconversion of rotational conformers and E / Z -isomers of tertiary anilides in great detail . Despite the remarkable utility of secondary anilides as auxiliary groups in asymmetric synthesis, the dynamic stereochemistry of this structural motif remains largely unexplored …”
Section: Introductionmentioning
confidence: 99%